2004
DOI: 10.1002/ejoc.200400073
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thienodolin

Abstract: We report a total synthesis of the alkaloid thienodolin (1a), as well as its 5-chloro isomer 1b and its unsubstituted analogue 1c, in three steps from the corresponding oxindoles 8a−c. The preparation was achieved through an initial Vilsmeier−Haack−Arnold reaction (chloro-formylation) followed by protection at the indole nitrogen, creation of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…The mixture was cooled, poured into ice water and basified with 30% NH 4 OH 32. The aldehyde 2d was collected by filtration with a yield of 30%: mp 180–190°C dec.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was cooled, poured into ice water and basified with 30% NH 4 OH 32. The aldehyde 2d was collected by filtration with a yield of 30%: mp 180–190°C dec.…”
Section: Methodsmentioning
confidence: 99%
“…[4] The total chemical synthesis was accomplished in three steps starting from 6-chlorooxindole. [5] Thienodolin was the first actinomycete metabolite to show concentration-dependent growth-regulating activity in rice seedlings.G rowth was promoteda tl ow concentrations ( 1.2-12 mm), but inhibited at higherc oncentrations (> 40 mm). [4] It is of significant pharmaceutical interest, because recently it was demonstrated that thienodolin exhibits anti-inflammatory and anti-tumor activity through suppression of nitric oxide synthases.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our ongoing studies of the chemical and biological properties of linear hetero[b]fused indoles [1][2][3][4], we have developed effective and simple methods for the synthesis of pharmacologically interesting pyridazino [4,3b]indoles [5], pyrano [3,2-b]indoles [6], pyrrolo [3,2-b] indoles [7], imidazo [4,5-b]indoles, thiazolo [5,4-b]indoles [8], and some of their analogs [9,10]. A number of representatives of these series displayed antituberculosis, monoamine oxidase inhibiting, antiviral, antihypoxic, and hepatoprotective activities some of which may be attributable to monoamine oxidase inhibition.…”
Section: Introductionmentioning
confidence: 99%